The Roles of Intellectual Intelligence, Emotional Intelligence, and Spiritual Intelligence in Efforts to Enhance Learning Achievement - Tamriatin Hidayah (LPPM Institut Teknologi dan Sains Mandala, 2025)
This research aims to test and analyze the influence of Intellectual Intelligence, Emotional Intelligence and Spiritual Intelligence on learning achievement through learning interests. The sample used was 171 students of Mandala Institute of Technology and Science. Data analysis uses descriptive statistics and inferential analysis. The sampling method is two stage sampling. The data analysis method use Smart PLS. The results of the study show that both Intellectual Intelligence, Emotional Intelligence and Spiritual Intelligence direct effect on learning achievement. The variable of learning interest does not play a role intervening variable. Important implication of this finding is the need to adjust the learning method to the characteristics of the course, student characteristics and strive to select learning methods that encourage students to be more enthusiastic about learning. In addition, it also necessary to improve the soft skills of students the Mandala Institute of Technology and Science.